Impact of an immersive, interactive medical education initiative on guideline-based retinal disease management knowledge/competence and effectual practice change - Singh, Rishi P.; Welch, Lauren; Longo, Nicole L.; Frese, Matt (BMC ophthalmology, 2023)
Background Retinal diseases, including wet or dry age-related macular degeneration, diabetic macular edema, and diabetic retinopathy (DR), are underdiagnosed and undertreated in the United States. Clinical trials support the effectiveness of anti-vascular endothelial growth factor (anti-VEGF) therapies for several retinal conditions, but real-world data suggest underuse by clinicians, resulting in patients experiencing poorer visual outcomes over time. Continuing education (CE) has demonstrated effectiveness at changing practice behaviors, but more research is needed to understand whether CE can help address diagnostic and treatment gaps. Methods This test and control matched pair analysis examined pre-/post-test knowledge of retinal diseases and guideline-based screening and intervention among 10,786 healthcare practitioners (i.e., retina specialists, ophthalmologists, optometrists, primary care providers, diabetes educators, pharmacists/managed care specialists, and other healthcare providers, such as registered nurses, nurse practitioners, and physician assistants) who participated in a modular, interactive CE initiative. An additional medical claims analysis provided data on practice change, evaluating use of VEGF-A inhibitors among retina specialist and ophthalmologist learners (n = 7,827) pre-/post-education, compared to a matched control group of non-learners. Outcomes were pre-/post-test change in knowledge/competence and clinical change in application of anti-VEGF therapy, as identified by the medical claims analysis. Results Learners significantly improved knowledge/competence scores on early identification and treatment, identifying patients who could benefit from anti-VEGF agents, using guideline-recommended care, recognizing the importance of screening and referral, and recognizing the importance of early detection and care for DR (all P -values = 0.003 to 0.004). Compared with matched controls, learners’ incremental total injections for anti-VEGF agents for retinal conditions increased more after the CE intervention ( P < 0.001); specifically, there were 18,513 more (new) anti-VEGF injections prescribed versus non-learners ( P < 0.001). Conclusions This modular, interactive, immersive CE initiative resulted in significant knowledge/competence gains among retinal disease care providers and changes in practice-related treatment behaviors (i.e., appropriate consideration and greater incorporation of guideline-recommended anti-VEGF therapies) among participating ophthalmologists and retina specialists compared to matched controls. Future studies will utilize medical claims data to show longitudinal impact of this CE initiative on treatment behavior among specialists and impact on diagnosis and referral rates among optometrists and primary care providers who participate in future programming.